Factors influencing the intention to stay amongst medical academic staff - Abdul Malek, A Tambi; Rabiatul Adawiyah, Muslim; Nur Lailatul Husna, M. Yusof; Md Nor Hayati, Tahir (2017)
The research was concerned with an age-old issue plaguing Malaysia where medical specialists in the public sector, including academics, quitted their job to join the private medical practice where they could earn a much higher income. The federal government responded to the situation by offering them direct entry to senior academic position, rapid career promotion, and special allowance. The financial package was, however, very far from what the private sector could offer. Nevertheless, many specialists chose to teach and develop their career in the university. An objective of the research was to identify the factors that influenced them to stay in their job. The outcome of the research would help universities ensure the availability of medical academic staff to conduct teaching and learning activities. A questionnaire survey of forty-seven medical lecturers was carried out at a public university to collect data on employee retention factors and intention to stay. The supposed relationship between the two was analysed using logistic regression. It was concluded that intention to stay was significantly influenced by job autonomy. The factor was made up of timeliness in the communication of organisational goals and freedom of thought and action in carrying out job responsibilities.